Comparación in vitro del desgaste compensatorio de tres instrumentos de acceso (Gates Glidden, IntroFile FlexMaster® y SX ProTaper®) utilizados en endodoncia - Vargas Mateos, Shiovan Yamileth (2014)
Objective: This in vitro study aimed to compare preflaring of three instruments of access with Gates Glidden, IntroFile FlexMaster® and SX ProTaper® used in endodontic treatment. Materials and methods: The preflaring was performed over 30 plastic upper molars (VDW, Germany) standardized which were divided into three groups of ten. Teeth were divided and implemented with Gates Glidden, IntroFile FlexMaster® and SX ProTaper® . This procedure was done by a single trained operator. For measuring the root canals, crowns of teeth were cut transversely to UCA level with a fine diamond disc. Measures corresponding to 5 anatomical references were evaluated: remaining mesial of mesiobuccal canal, vestibular of mesiobuccal canal, mesial of distobuccal canal, vestibular of distal canal and distance between wall of distal of mesiobuccal canal with wall of mesial of distalbuccal canal. The results were analyzed in microns (µm) through a stereomicroscope with a Leica Microsystems 56D software. Results: Statistically significant differences between experimental groups were found. Introfile limes produce minor discrepancy of compensatory attrition. The main discrepancy was found in group 1 (Gates Glidden) unlike the other instruments. Conclusions: The IntroFile FlexMaster® limes present lower cutting angle which produce a conservative preflaring in comparison to Gates Glidden strawberries which produce a more aggressive preflaring.